EFFECTIVENESS OF UTILIZATION OF CLASS II BITUNG PLP RESOURCES IN IMPLEMENTING MARITIME SAFETY - Yehezkiel Silitonga; Fitri H. Mamonto; Devie S. R. Siwij (PT. Radja Intercontinental Publishing, 2026)
The purpose of this study is to analyze the effectiveness of the utilization of PPLP Class II Bitung resources in implementing maritime safety. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. Research informants consisted of structural officials, operational officers, and administrative staff directly involved in the implementation of maritime safety tasks. Data analysis was carried out through data reduction, data presentation, and systematic drawing of conclusions. The results of the study indicate that the effectiveness of resource utilization is not yet fully optimal. From the human resources aspect, there are limitations in numbers and competencies that are not evenly distributed. From the aspect of facilities and infrastructure, there are still limitations in numbers and conditions that are not optimal. From the budget aspect, limited allocations and administrative constraints affect operational implementation. Supporting factors include human resource commitment and inter-agency cooperation, while inhibiting factors include limited resources and complex bureaucracy. The conclusion of this study indicates that the effectiveness of resource utilization is influenced by the alignment between organizational capacity and operational demands. The implications of this study emphasize the need to improve human resources, strengthen facilities, optimize budgets, and improve managerial and coordination systems.